Acoustic echo cancellation by minimising mutual information within sliding DFT window. Issue 25 (1st December 2013) - Gower, E.S.; Hawksford, M.O.J.
Abstract : An acoustic echo cancellation (AEC) algorithm based on minimising the mutual information between the loudspeaker and system output signals over a sliding discrete Fourier transform (DFT) window, for single AEC parameter estimation, is introduced. Unlike the conventional least‐mean‐square (LMS) systems, the proposed algorithm requires no double‐talk detection (DTD) and its AEC parameter can be continually updated. Although it has been shown that independent component analysis (ICA) allows continual adaptation of the AEC parameters under DTD, current ICA‐based algorithms estimate a filter of the same length as that of the LMS techniques. The sliding DFT window is utilised to facilitate adaptation of only one AEC parameter for deflation of the far‐end signal, thereby greatly reducing the computational load.